Editorial - Quispe-Salcedo, Angela (2018)
Dental education comprises a variety of competences and fine motor skills that must be acquired by students not only in the classroom but also in preclinical laboratories and dental clinics. In Peru, the average duration of dental undergraduate programs is five years. While it is true that curriculums vary from one school to another, preclinical and clinical activities are usually initiated during the third and fifth semesters, respectively. While the curriculums of Peruvian dental school programs tend to emphasize the importance of know-how and clinical training, undergraduate students are also trained in complementary skills that enable them to deepen their understanding of the profession beyond the dental chair.